Effects of Ketamine on EEG in Baboons with Genetic Generalized Epilepsy - Gowda, Shaila (Epilepsy Res, 2019)
Ketamine, a noncompetitive N-methyl-D-aspartate receptor (NMDAR) antagonist, used as an anesthetic has been reported to induce seizures both in humans and baboons predisposed to epilepsy. In this study, we aimed to characterize the acute effects of ketamine on scalp (sc-EEG) and intracranial EEG (ic-EEG) in the baboon, which offers a natural model of genetic generalized epilepsy (GGE). We evaluated the electroclinical response to ketamine in three epileptic baboons. The raw EEG data were analyzed within 10 minutes of intramuscular ketamine (5–6 mg/kg) administration. Earliest EEG changes occurred after 30 seconds in sc-EEG and after 15 seconds in ic-EEG of ketamine administration. These initial changes involved increased paroxysmal fast activity (PFA) followed by slowing, the latter emerging first occipitally, and then spreading more anteriorly. Generalized spike-and-wave discharges (GSWDs) were evident on both sc-EEG and ic-EEG within two minutes, but focal occipital discharges were already increased on ic-EEG after 15 seconds. Occipital slowing emerged on icEEG after 30 seconds, before spreading fronto-centrally and orbito-frontally. By 60–120 seconds post-injection, ic-EEG demonstrated a parieto-occipital burst suppression (BS), which was not noted on sc-EEG. Ketamine waves and seizures, especially if the latter were subclinical, also appeared earlier on ic-EEG. This study highlights the anesthetic and proconvulsant effects of ketamine originate in the occipital lobes before fronto-central regions. We speculate that NMDAR concentration difference in cortical regions, such as the occipital and frontal cortices, are mainly involved in the expression of ketamine’s EEG effects, both physiological and epileptic.